Cost-effectiveness analysis of ixekizumab versus secukinumab in patients with psoriatic arthritis and concomitant moderate-to-severe psoriasis in Spain. Issue 8 (13th August 2020) - Schweikert, Bernd; Malmberg, Chiara; Núñez, Mercedes; Dilla, Tatiana; Sapin, Christophe; Hartz, Susanne
Abstract : Objective: To conduct a cost-effectiveness analysis from the perspective of the Spanish National Health System (NHS) comparing ixekizumab versus secukinumab. Design: A Markov model with a lifetime horizon and monthly cycles was developed based on the York model. Four health states were included: a biological disease-modifying antirheumatic drug (bDMARD) induction period of 12 or 16 weeks, maintenance therapy, best supportive care (BSC) and death. Treatment response was assessed based on both Psoriatic Arthritis Response Criteria (PsARC) and ≥90% improvement in the Psoriasis Area Severity Index score (PASI90). At the end of the induction period, responders transitioned to maintenance therapy. Non-responders and patients who discontinued maintenance therapy transitioned to BSC. Clinical efficacy data were derived from a network meta-analysis. Health utilities were generated by applying a regression analysis to Psoriasis Area Severity Index and Health Assessment Questionnaire‒Disability Index scores collected in the ixekizumab SPIRIT studies. Results were subject to extensive sensitivity and scenario analysis. Setting: Spanish NHS. Participants: A hypothetical cohort of bDMARD-naïve patients with psoriatic arthritis and concomitant moderate-to-severe psoriasis was modelled. Interventions: Ixekizumab and secukinumab. Results: Ixekizumab performed favourably over secukinumab in the base-case analysis, although cost savings and quality-adjusted life-year (QALY) gains were modest. Total costs were €153 901 compared with €156 559 for secukinumab (difference −€2658). Total QALYs were 9.175 vs 9.082 (difference 0.093). Base-case results were most sensitive to the annual bDMARD discontinuation rate and the modification of PsARC and PASI90 response to ixekizumab or secukinumab. Conclusion: Ixekizumab provided more QALYs at a lower cost than secukinumab, with differences being on a relatively small scale. Sensitivity analysis showed that base-case results were generally robust to changes in most input parameters. Trial registration number: SPIRIT-P1: NCT01695239 ; Post-results, SPIRIT-P2: NCT02349295 ; Post-results.